Digital-Based Learning Evaluation Model for High School Students - Roza, Ahmad Subhan; Dewi, Asih Fitriana; Wahyuni, Sri (Universitas Pendidikan Mandalika, 2024)
This research aims to develop a digital-based learning evaluation model for Senior High School students. This research method used a design research approach with a development study type. This research followed the model developed by Tessmer, which includes the stages of preliminary and formative evaluation. The formative evaluation stage encompasses self-evaluation, prototyping (expert review, one-to-one, and small group), as well as field testing. The data collection techniques for this research involved interviews and questionnaires, with data analysis conducted through both quantitative and qualitative methods. The results of this study indicated that the material validation score was 95.33%, categorized as